The Linked-In book for network marketing simple strategies for massive success - Aaron, Scott (Ascent Audio, 2020)
A step-by-step system of how network marketers, direct sales associates, and multi-level marketers can utilize LinkedIn to grow their businesses, leads, teams, and bank accounts. This book has helped thousands of network marketers, entrepreneurs, and individuals experience explosive growth following the program featured in this book. Scott's strategic approach to teaching others how to create wealth online is people-focused and results driven, with a focus on organic traffic, a game changer when it comes to competing in a saturated digital world. Internationally acclaimed and award-winning network marketer, business coach, best selling author and speaker Scott Aaron is the go-to specialist when it comes to converting traffic, establishing connections, creating residual income using LinkedIn(r), and building personal brands. Having started his own network marketing business just six years ago, Scott saw massive opportunities that the internet had to offer. Fully immersing himself in learning LinkedIn(r) and social media strategies, Scott quickly gained traction as a leader in generating big results for other network marketers, online business owners and internet marketers, while generating a multiple six-figure business himself. Scott is passionate about helping fellow network marketers achieve success while building their own network organically and without complicated and costly marketing tactics.
Online resource; title from title details screen (O'Reilly, viewed February 28, 2023)
Keywords: LinkedIn (Electronic resource); Business networks -- Computer network resources; Internet marketing; Online social networks; Marketing sur Internet; Réseaux sociaux (Internet); Business networks; Computer network resources; Audiobooks; Livres audio